e-Student Residential Hall Management Model (eSRHMM) - Musse, Yahia Ali (2010)
A key factor which makes Web Based Applications (WBA) highly recommended over stand alone system is centralized mechanism used in those applications. Students' Residential Hall managements in Universiti Utara Malaysia (UUM) use variety of systems which are mostly mixture of WBA and some manual procedures. This study would try to enhance the process of the current management procedures by converting it entirely into a WBA which would solve some of the critical issues which are not supported by the current system. The proposed system would adopt Extreme Programming (XP) and Rational Unified Process (RUP) methodology in order to fulfill its objectives.